Business judgement rule: a new defense for business and management decisions by company directors? - Azmi, Ruzita; Abd Razak, Adilah (2012)
A legal effect of the incorporation of a company is that the company is an artificial person with separate legal personality possessing rights and obligations distinct from those of its members and officers. Being an artificial person with separate legal personality it can only be represented by, or act through the intermediary of humans. The two main organs of human agencies through which a company can operate are the shareholders or members acting together in a general meeting and the board of directors (BOD): these two organs are its primary decision-making bodies. The BOD bestowed with management powers are expected to steer the company towards long-term sustainability. The business judgment and management decision by those directors involve risk taking, and such judgment or decision may go wrong and cause loss to the company. It is right for company’s directors to be protected over a business judgment that has gone wrong if they had applied their judgment with responsibility, honesty and in the best interest of the company. The High Level Finance Committee on Corporate Governance in their Report of Corporate Governance (RCG) published in February 1999 observed the existence of a business judgment rule (BJR) to safeguard directors in the United States and Australia proposed a similar statutory formulation of BJR for Malaysia. When Malaysia carried out the first major attempt at updating the Companies Act (CA) 1965 via the Companies (Amendment) Act 2007, several changes were made to the law relating to duties of directors. Most importantly, the CA 1965 has accepted the recommendation made by RCG as seen in section 132 (1 B) whereby a new concept of ‘BJR’ is introduced. This paper examines the BJR in Malaysia. It also compares the concept of BJR between Malaysia, United States and Australia. This paper also aims to evaluate how far the courts have gone in using the rule to protect the business and management decisions by company directors.